2008
DOI: 10.1016/j.mce.2007.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Liquiritigenin is a plant-derived highly selective estrogen receptor β agonist

Abstract: After the Women's Health Initiative found that the risks of hormone therapy outweighed the benefits, a need for alternative drugs to treat menopausal symptoms has emerged. We explored the possibility that botanical agents used in Traditional Chinese Medicine for menopausal symptoms contain ERbeta-selective estrogens. We previously reported that an extract containing 22 herbs, MF101 has ERbeta-selective properties. In this study we isolated liquiritigenin, the most active estrogenic compound from the root of Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
175
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(182 citation statements)
references
References 48 publications
6
175
1
Order By: Relevance
“…Second, liquiritigenin has been shown in several studies to exert cytoprotective effects [16,17] ; recent studies demonstrate that liquiritigenin exerts anti-inflammatory effects through the NF-κB pathway [18] . Third, we previously observed that liquiritigenin did not induce proliferation of MCF-7 and T47D breast cancer cells (data not shown), which is consistent with other studies [13] . Finally, pharmacokinetic studies from our laboratory have demonstrated that liquiritigenin exhibits good intestinal absorption and blood-brain barrier permeability [19] .…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…Second, liquiritigenin has been shown in several studies to exert cytoprotective effects [16,17] ; recent studies demonstrate that liquiritigenin exerts anti-inflammatory effects through the NF-κB pathway [18] . Third, we previously observed that liquiritigenin did not induce proliferation of MCF-7 and T47D breast cancer cells (data not shown), which is consistent with other studies [13] . Finally, pharmacokinetic studies from our laboratory have demonstrated that liquiritigenin exhibits good intestinal absorption and blood-brain barrier permeability [19] .…”
Section: Introductionsupporting
confidence: 92%
“…Our interest in liquiritigenin developed as a result of the following observations. First, liquiritigenin was shown to be a highly selective agonist of estrogen receptor-β (ERβ) [13] , an observation that is consistent with our previous findings (unpublished data). ERβ is expressed in brain centers related to learning and memory and is less likely than ERα to be related to sexual function [14,15] .…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Liquiritigenin is a component of a Chinese herb that is currently in clinical trials for the treatment of postmenopausal symptoms (28). This compound binds to ER␣ and ER␤ with similar affinity but induces the transcriptional activation of ER␤ specifically.…”
Section: Comparison Of Natural Er Ligands Via Bretmentioning
confidence: 99%
“…EC, the contraceptive measures that can be taken after sex to prevent pregnancy (Sander et al 2009), is a popular form of reversible contraception. Oestrogens and progestins, individually or in combination, and antiprogestins form the active constituents of the currently available major hormonal EC formulations (Farrar et al 2003), but continuous usage of these formulations has undesirable effects that include the proliferative actions of oestrogenic component (Mersereau et al 2008) or higher failure rate and menstrual abnormalities associated with progestogen-only pills (Ahrendt et al 2010). Development of a safe and effective non-steroidal contraceptive formulation is therefore recognised as a global need of the day.…”
Section: Introductionmentioning
confidence: 99%